A novel truncated variant in SPAST results in spastin accumulation and defects in microtubule dynamics - Jie Wang; Yihan Wu; Hong Dong; Yunpeng Ji; Lichun Zhang; Yaxian Liu; Yueshi Liu; Xin Gao; Yueqi Jia; Xiaohua Wang (BMC, 2023)
Abstract Objective Haploinsufficiency is widely accepted as the pathogenic mechanism of hereditary spastic paraplegias type 4 (SPG4). However, there are some cases that cannot be explained by reduced function of the spastin protein encoded by SPAST. The aim of this study was to identify the causative variant of SPG4 in a large Chinese family and explore its pathological mechanism. Materials and methods A five-generation family with 49 members including nine affected (4 males and 5 females) and 40 unaffected individuals in Mongolian nationality was recruited. Whole exome sequencing was employed to investigate the genetic etiology. Western blotting and immunofluorescence were used to analyze the effects of the mutant proteins in vitro. Results A novel frameshift variant NM_014946.4: c.483_484delinsC (p.Val162Leufs*2) was identified in SPAST from a pedigree with SPG4. The variant segregated with the disease in the family and thus determined as the disease-causing variant. The c.483_484delinsC variant produced two truncated mutants (mutant M1 and M87 isoforms). They accumulated to a higher level and presented increased stability than their wild-type counterparts and may lost the microtubule severing activity. Conclusion SPAST mutations leading to premature stop codons do not always act through haploinsufficiency. The potential toxicity to the corticospinal tract caused by the intracellular accumulation of truncated spastin should be considered as the pathological mechanism of SPG4.